Étude des effets de l'agriculture de conservation par rapport à l'agriculture traditionnelle - Escribano J. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
The objective of this study is to highlight the problems that may result from a traditional management of the soil, based on intensive tillage, and the use of extensive crops as well as to explain the advantages in using conservation agriculture (saving of water and fertilizers and soil improvement).
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)